1996
DOI: 10.1590/s0102-311x1996000400007
|View full text |Cite
|
Sign up to set email alerts
|

As implicações do conhecimento prático para a vigilância em saúde do trabalhador

Abstract: Neste artigo, discute-se a vigilância em saúde do trabalhador enquanto uma ação em saúde motivada pelo conhecimento dos trabalhadores. O trabalho parte da noção de vigilância à saúde (especialmente no conceito de problema) e de conhecimento prático, tomando por base a teoria das representações sociais. Assim ancorado, desenvolve a concepção de que a formulação de problema de saúde é uma representação social e, como tal, segue uma lógica peculiar. Essas reflexões são incorporadas à discussão da prática do mapea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
28

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 2 publications
0
3
0
28
Order By: Relevance
“…Besides, they thought that the job required constant mental concentration and that they were under pressure on jobs, exerted by workmates, the immediate boss, or the employer. Thus, the findings of literature were corroborated, pointing out that the context of RSI/ WMSD is grounded on an organization of labor activity based on pressure for productivity, under low pay and poor work conditions, where workers had little control over the production methods (Sato, 1996;Batista et al, 1998;Neves, 2006 It is also worth noticing that patients with RSI/ WMSD reported in detail the obstacles for defining diagnosis and accessing treatment, related to the unpreparedness of professionals at the health care system (public and private) for providing a proper anamnesis of the clinical condition, a factor which postponed the onset of treatment and the request for sick leave. According to them, the correct procedure was observed in public services with professionals specialized in occupational health.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Besides, they thought that the job required constant mental concentration and that they were under pressure on jobs, exerted by workmates, the immediate boss, or the employer. Thus, the findings of literature were corroborated, pointing out that the context of RSI/ WMSD is grounded on an organization of labor activity based on pressure for productivity, under low pay and poor work conditions, where workers had little control over the production methods (Sato, 1996;Batista et al, 1998;Neves, 2006 It is also worth noticing that patients with RSI/ WMSD reported in detail the obstacles for defining diagnosis and accessing treatment, related to the unpreparedness of professionals at the health care system (public and private) for providing a proper anamnesis of the clinical condition, a factor which postponed the onset of treatment and the request for sick leave. According to them, the correct procedure was observed in public services with professionals specialized in occupational health.…”
Section: Resultsmentioning
confidence: 85%
“…For analyzing this "symbolic meeting", we used the social representations framework. For patients with RSI/WMSD, as well as for medical experts, who construct representations of themselves and the "other" through the expert medical consultation context, here understood as a singular context, the theoretical framework provided by the inclusion of subjects' practical knowledge reasoning into the social representations framework is of great importance in the occupational health field (Sato, 1996).…”
Section: Rsi/wmsd and The Social Representations Fieldmentioning
confidence: 99%
“…(DEJOURS, 1999;WISNER, 1994;GUÉRIN, et al, 2001;DANIELLOU, 2004;SZNELWAR, 2004;SATO, 1996;VILELA, 2003VILELA, , 2010 Além disso, as ações em VISAT, segundo a Rede Nacional de Atenção Integral à Saúde do Trabalhador (RENAST) (BRASIL, MS, 2002), devem ocorrer a partir da noção de problema e da percepção e conhecimento do próprio trabalhador sobre as condições e organização do trabalho. Nessa pesquisa verifi cou-se que há um distanciamento entre esses pressupostos e o que as autoridades sanitárias fazem na prática.…”
Section: Resultsunclassified
“…De acordo com Sato (1996), a explicitação de uma proposta de atuação nos locais de trabalho a partir do conhecimento dos trabalhadores não é uma prática nova, mas merece ser discutida. Para a autora, apesar do MOI ter inspirado a obrigatoriedade de elaboração do Mapa de Riscos Ambientais pelas Comissões Internas de Prevenção de Acidentes -Cipas (BRASIL, 1995), é necessário aprofundar a discussão acerca da epistemologia que combina conhecimento prático e conhecimento científico.…”
Section: O Modelo Operário Italiano E Seu Legadounclassified